Sexual Minorities and Majorities: A Pending Assingment for Psychology and Formal Education in Peru - Braun, Ricardo (2021)
This essay examines the current situation of formal inclusion of sexual minorities in primary and secondary schools in Peru. There is no inclusion, therefore, psychology as a science has a pending task of intervening to overcome the situation. As the knowledge about sexuality comes from popular psychology and the teachers lack scientific knowledge about sexuality in general, and therefore, are not able to convey proper teaching to their pupils in charge, psychologists have the task to help teachers to implement the Ministry of Education of Peru´s Integral Sexual Education program. I analyze the concept of folk psychology to better understand the difference between an intuitive explanation of sexuality versus an informed scientific one. I propose at thethird paradigm in the analysis of adolescent sexual minorities That doesn't replace, but complements, the former ones, the paradigm of the context of the sexual minority.